Artificial Intelligence and Bias in Religious Auhtority - Hanik L. Tarwiyyah (Jurnal Informasi dan Teknologi, 2025)
This research examines the complex interaction between Artificial Intelligence (AI) and religious authority. The main focus of the study is the significant risk of algorithmic bias, which emerges as AI becomes increasingly integrated into various aspects of life, including the religious sphere. The potential for bias in AI systems can affect the interpretation of doctrine, religious education, and even the legitimacy of spiritual leadership. This study uses a qualitative approach through document analysis and case studies to understand how AI, defined as the ability of computational systems to mimic human intelligence, can inadvertently reinforce religious prejudices and stereotypes. The results show that AI bias can manifest in various harmful forms. These forms include religious stereotypes, religious misinformation or "hallucinations," and the reinforcement of existing prejudices. Furthermore, the study also found a transformation of religious authority from traditional to digital, influenced by algorithmic logic and metric culture. In response to these challenges, various religious authorities have issued ethical guidelines emphasizing the importance of human responsibility, transparency, accountability, and the protection of human dignity in the development and use of AI